Retrospective Analysis of the Outcomes of Children with Congenital Diaphragmatic Hernia Treated with Different Surgical Techniques - Yadav, Ramdhani; Nath, Nagendra; Prasad, Ramjee; Kumar Thakur, Vinit (Journal of Neonatal Surgery, 2025)
Background: Congenital diaphragmatic hernia (CDH) is a life-threatening neonatal condition characterized by a defect in the diaphragm allowing abdominal organs to herniate into the thoracic cavity, leading to pulmonary hypoplasia and respiratory distress. Surgical repair remains the definitive treatment, performed either through open or thoracoscopic approaches. This study aims to evaluate the outcomes of open versus thoracoscopic CDH repair in neonates at a tertiary care center. Methods: A retrospective observational study was conducted on 40 neonates diagnosed with CDH and treated surgically between January 2021 and December 2024. Clinical data including demographics, hernia characteristics, “surgical approach, intraoperative findings, complications, length of hospital stay, and mortality were collected and analyzed. Results: Among the 40 patients, 30 (75%) underwent open repair and 10 (25%) underwent thoracoscopic repair. Left-sided hernias were predominant (80%), with a male-to-female ratio of 1.35:1. Patch repair was required in 6.7% of cases, mostly in the open repair group (75%). The overall mortality rate was 15%, with higher mortality observed in the open group (16.7%) compared to the thoracoscopic group (10%). The average hospital stay was significantly shorter in the thoracoscopic group (14 days) compared to the open group (21 days). Hernia recurrence occurred in 10% of cases, exclusively in the thoracoscopic repair group. Postoperative complications were more frequent in the open repair group (20%) than the thoracoscopic group (13%). Conclusion: Thoracoscopic repair of CDH is a safe and effective alternative to open repair, associated with lower mortality, shorter hospital stay, and fewer postoperative complications. However, the risk of recurrence may be higher, warranting careful patient selection and long-term follow-up.